Pengaruh Lingkungan Keluarga terhadap Perkembangan Moral Peserta Didik - Rofiatun Nisa’; Yusnia Dwi Lindawati; Juri Wahananto (PUSAT PENELITIAN DAN PENGABDIAN KEPADA MASYARAKAT (P3M) SEKOLAH TINGGI ILMU TARBIYAH AL-FATTAH SIMAN LAMONGAN, 2020)
The role of parents in guiding the growth of their children from an early age becomes very important for the future life and education of their children. Where in childhood is the most important because it is the foundation of personality that determines the child's next experience. The purpose of this study was to determine the level of the students 'family environment, students' moral development, the influence of the family environment on the moral development of Class V in MI Miftahul Ulum Pelangwot in the 2019 school year. This study was a correlative quantitative study with data collection methods through a questionnaire, and documentation. Data analysis techniques include descriptive analysis, simple linear regression analysis, t test and coefficient of determination. The family environment of class V students in Mi Miftahul Ulum Pelangwot Laren is in the good category, and the moral development of class V students in the category is very good, from the results of t-regression regression analysis obtained tcount> ttable (2.335> 1.761) then Ha is accepted and can be concluded that partially the family environment variable has a significant effect on the moral development of students, meaning that the better the family environment, the better the moral development of students.